A Study on Enhancing Logistics Efficiency Through Supply Chain Informationization: The Case of Hefei Reying International Trade Co., Ltd. - Jing Bao (Journal of World Economy, 2025)
This paper delves into how Hefei Reying International Trade Co., Ltd. enhances logistics efficiency through supply chain informationization. Firstly, it analyzes the importance of supply chain informationization in e-commerce, highlighting its key role in improving supply chain transparency, response speed, and resource allocation efficiency. Then, it details Hefei Reying’s specific practices in the application of supply chain management software, automation tools, and supply chain data analysis and decision support. Through these informationization measures, the company has successfully automated order processing, refined inventory management, and made decision support more scientific, significantly improving logistics efficiency, reducing operational costs, and enhancing customer service levels. The paper concludes with a summary of the achievements and experiences in Hefei Reying’s supply chain informationization practice, providing valuable references for other e-commerce enterprises.